His bundle pacing preserves left ventricular ejection fraction in patients with conduction disease and high risk of development pacing induced cardiomyopathy. (25th November 2020) - Mizner, J; Curila, K; Stros, P; Prochazkova, R; Vesela, J; Karch, J; Herman, D; Osmancik, P; Widimsky, P
Abstract: Background: His bundle pacing (HBP), contrary to right ventricular myocardial pacing (RVP), offers the most physiological activation of both ventricles and may not lead to pacing induced cardiomyopathy. The change in myocardial structure in failing heart due to myocardial pacing should be reflected in plasmatic levels of collagen metabolism biomarkers and inflammation markers. Purpose: To compare a difference in the left ventricular ejection fraction (LVEF) and levels of selected biomarkers between two groups: HBP and RVP (preferably septal). Methods: Eighty-six patients with conduction disease indicated to permanent cardiac pacing were randomized to HBP or RVP. Only high-risk patients for pacing induced cardiomyopathy development were included. Blood sampling and echocardiography were performed on the consequent day and 180 days after the pacemaker implantation. The measured biomarkers were: matrix metalloproteinase 9 (MMP-9), tissue inhibitor of metalloproteinase 1 (TIMP-1), galectin-3 (GAL3), ST2/IL-33R (ST2/IL) and TGF-beta 1 (TGFβ1). Statistical analysis included Students t-test, Fishers exact test and Chi-squared test. The p<0.05 was considered to be statistically significant. Results: First group included 39 patients with HBP (selective or non-selective His bundle capture) and 47 patients with RVP. Both groups were similar with respect to gender, LVEF, QRS duration and the baseline levels of evaluated biomarkers. In both groups, there was a high burden of ventricular pacing after 6 months (above 90%) (p = NS). The ejection fraction of the left ventricle did not change in the HBPgroup (60 vs 60%, p=0, 3), but it decreased significantly in the RVP group (59 vs 56%, p=0, 004). The decline in the LVEF of at least 5% occurred in 12 patients (26%) from RVP group, compared to 3 patients (8%) in HBP group (p=0, 03). The blood levels of dMMP-9 (p=0, 02), TIMP-1 (p=0, 003), ST2/IL (p=0, 003) and TGFβ1 (p=0, 021) declined significantly after 180 days in the HBP group, decline of Galectin 3 was nonsignificant. In the RVP group, there was a significant decline in blood levels of MMP-9 (p=0, 014), TIMP-1 (p=0, 001) and ST2/IL (p= 0, 04), decline of Galectin 3 and TGFβ1 was nonsignificant. The biomarker level difference was not statistically significant between the two groups. Conclusion: His bundle pacing, contrary to right ventricular myocardial pacing, preserves LVEF in patients with high risk of pacing induced cardiomyopathy development. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Charles University research programme. Q38. UNCE/MED/002